Jakość w perspektywach strategicznej karty wyników - Markowska, Małgorzata (Quality in Prospects of Balanced Scorecard, 2006)
This paper shows that it is possible to use the balanced scorecard in TQM strategy. Quality costs are very important measures in prospects of balanced scorecard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 58-63